Phytochemistry and anti-microbial property of panikoorka - Shankar H R (Department of Plantation Crops and Spices,College of Horticulture, 2006)
An experiment was conducted at the Department of Plantation Crops and Spices, College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during 2003-2005 to study the influence of stage of harvest, drying method and method of extraction and storage on phytochemistry and antimicrobial property of Coleus amboinicus Lour.